Chimica e fascismo: Il contributo epistemologico e culturale di Giovanni Battista Bonino (1899 - 1985) durante gli anni del fascismo - Karachalios, Andreas (Chimica nella Scuola, 2022)
The aim of this paper is to draw a picture of Giovanni Battista Bonino’s (1899 - 1985) important research efforts, in order to better assess his path-breaking papers on quantum chemistry. The focus is on Bonino’s innovative amalgamation of organic chemistry with quantum physics and group theory. At the same time, his portrait with a glance at the cultural relations within the contemporary scientific community is discussed. Bonino obtained in the year 1927 the chair of Physical Chemistry at the University of Bologna, one of the first such chairs in Italy. He was also the first chemist in Italy at the beginning of the Twenties to perceive the importance of Infrared spectroscopy. Bonino began research in 1929 on Raman spectroscopy with the main objective of studying the constitution of organic compounds. In his work from 1929 to 1941, quantum chemistry emerged as a sub discipline of theoretical chemistry in Italy. The original contribution of Bonino consisted first in a new recommendation for a benzene formula with polarized double bonding, and second in the generalization of Werner’s concept of coordination. Moreover, this paper emphasizes the role of Bonino for the formation and strengthening of scientific and cultural relations between Italian fascism and German nationalism after the Rome-Berlin axis of 1936.